Applications of microdialysis in pharmaceutical science - Tsai, Tung-Hu (Wiley, 2011)
"This book emphasizes the applications of microdialysis in different organs and tissues for pharmacokinetic and pharmacodynamic studies, covering the range of current clinical uses for microdialysis. Along with details of the basics of this analytical technique, topics in the book include applications for drug discovery, analytical consideration of samples, neurological disease investigations, sampling at different organs, diabetes evaluations, tumor response estimations and comparison of microdialysis"--